STUCTURE STRENGTH ANALYSIS CONVENTIONAL PILE FIXED JACKET PLATFORM IN NATUNA SEA USING FINITE ELEMENT METHOD - Aditya, Berlian Arswendo; Elyanto, Redi Yuniansyah (Department of Naval Architecture - Diponegoro University, 2011)
Offshore Platform is a structure or construction which build in offshore territory to support the exploration process or the exploitation of mine. The main function of the offshore platform is to support the top construction including the operational facilities on the water during the operational time safely, in operational condition (normal) even in stormy condition. Modelling of the structure fixed jacket platform, the environment load and the analysis system using Finite Element Methode software. The environmental load (wind,wave,steam) according to 8 eyes wind (0â°, 45â°, 90â°, 135â°, 180â°, 225â°, 270â°, and 315â°). From the software analysis we can conclude that the biggest value of the Unity Check in stormy condition is 0.464 state in 766 member and the biggest value in Unity Check in operational condition is 0.396 state in 766 member. It is a good point because it suited with API RP2A WSD 2007, UC value (Unity Check) â‰¤ 1.00. So in operational condition even in stormy, fixed jacket platform still be able to withstand the materialÂ which is accepted. Another result from the minimum of Safety Factor in operational condition in 766 member has SF 2.00, beside in stormy condition which state in 766 member has 1.66 SF value. This result has a good point because it suited with API RP2A WSD 2007 which is in operational condition the minimum of SF value is 2.00 and in stormy condition the minimum of SF value is 1.5.